A Scalable, Decentralised Large-Scale Network of Mobile Robots for Multi-target Tracking - Pham, Duy Hung (ĐHCN, 2016)
A scalable, decentralised large-scale network of mobile robots for multi-target tracking is addressed in this paper. The decentralised control is originally built up by behavioural control but upgraded with decentralised robot control for connectivity maintenance and decentralised connectivity control for hierarchical connectivity removal, allowing the network expansion for tracking and occupying spatially distributed targets. The multi-target tracking algorithm guarantees that the mobile robots reach targets at very high efficiency, while at least an interconnectivity network connecting all the mobile robots is preserved for information exchange. The Monte Carlo simulation results illustrate characteristics of the decentralised control as well as its scalability through several experimental scenarios.